2019
DOI: 10.1101/577932
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cannabis-associated symptom profiles in patients with first episode psychosis and population controls

Abstract: ObjectiveThe evidence is mixed on whether cannabis use is associated with a particular symptomatology in first episode psychosis (FEP) patients.The authors set out to investigate a) patterns of association between cannabis use and transdiagnostic symptom dimensions; b) whether the extent of use of cannabis contributes to the variation in clinical and subclinical symptom profiles.MethodThe authors analysed data from 901 patients and 1235 controls recruited across six countries, as part of the European Network o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…In the general population, it was associated with both elevated psychoticism and detachment, although the latter effect was weaker 48,172‐174 . In patients, cannabis use was associated with more severe reality distortion symptoms and was not consistently linked to other symptoms 175‐179 .…”
Section: Validity Evidencementioning
confidence: 95%
“…In the general population, it was associated with both elevated psychoticism and detachment, although the latter effect was weaker 48,172‐174 . In patients, cannabis use was associated with more severe reality distortion symptoms and was not consistently linked to other symptoms 175‐179 .…”
Section: Validity Evidencementioning
confidence: 95%
“…Consistent with this methodology, we reported that transdiagnostic psychopathology at first episode psychosis (FEP) can be represented by a general psychosis factor (G), and five specific dimensions of positive (POS), negative (NEG), disorganization (DIS), manic (MAN), and depressive (DEP) symptoms (10). Similarly, a model composed of general and specific experience dimensions has been proposed to measure subclinical psychosis in the general population (11, 12). These conceptualizations statistically reflect a ‘bi-factor model’, where the general and specific dimensions account, respectively, for the unidimensional and multidimensional nature of the latent psychosis construct (13, 14).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we recently found evidence that cannabis-associated psychopathology at psychosis onset is characterised by high POS scores and low NEG scores (16). In relation to biological factors, symptom dimensions have been investigated in family, twin and adoption studies (17-22), overall showing that NEG or DIS symptoms had higher familial aggregation than other symptom dimensions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations